(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract:Tomato Leaf Curl viral Disease (TLCD) is a widely studied viral infection caused by the Geminivirus, TLCV, leading to enormous crop loss across the world. There are more than 21 varieties of the virus reported from India. However, each viral variety is specific in its infection pattern leading to variation in the survivability and symptoms development on the plant. To enable the invitro study of the virus it is therefore, mandatory to standardize the methods for mechanical infection of the virus. The current study therefore focuses on understanding the effect of age of plant, load of viral inoculums, pattern of inoculation including percentage leaves infected and effect of addition of charcoal during inoculation, on the symptoms development on the plant. From the above experiments an efficient in vitro-inoculation method for Tomato leaf curl virus on Lycopersicumesculentum was developed.